Rancang Bangun Dapur Pada Smart Home Dengan Fitur Speech Recognition Menggunakan Aplikasi Labview Berbasis NI myRIO 1900 - Hafizh Hamzah Wicaksono; Wijaya Kurniawan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Smart home technology is absolutely necessary because it can improve the quality of life of a human being. In Indonesia, the smart home technology is currently still slow if compared to neighboring countries such as Singapore, Australia, and Malaysia. In addition, many of users do not understand the procedures and cooking recipes. Based on these problems, development smart home technology especially in the kitchen is necessary. Researchers use NI myRIO 1900 as mikrokontroler, labview and microsoft visual studio as a software development program. In this research there are 5 features that is (1) Turns on and off lamp automatically using PIR(Passive Infared Reciver) sensors. (2) Turn on and off the water faucet automatically using IR(Infared Reciver) obstacle sensor. (3) Detection when there is fire in the kitchen using flame sensors. (4) Closes the refrigerator door automatically by using a Motor DC. (5) Search recipe that uses speech recognition technology. After the researchers, there are several conclusions. the first, measuring accuracy of the PIR sensor to reach 83% by movement of hands on a prototype kitchen as much as 6 times the experiment. Second, that measure the level of accuracy of the sensor IR obstacle to reach 86% by way of doing the hands on approach to tap water as much as 6 times the experiment. Third, that measures the level of accuracy of the flame sensor reaches 86% by the way put a candle flame as much as 6 times the experiment. Fourth, measuring the level of accuracy of speech recognition to reach 83% by way of pronouncing the words that have been registered as many as 15 times.